Alternative Assessment and Its Impact in the Classroom of English on Speaking Skill at Elementary School - Novita Mutiah Yudha; Ahmad Munir; Lies Amin Lestari; Syafi’ul Anam (Institut Agama Islam Negeri Palopo, 2022)
This paper aims to investigate how the students in Elementary school have an impact after the teacher doing an alternative assessment in the classroom of the English language. The author conducts this research about alternative assessment at Elementary school. The participant in this study was an English teacher. Elementary school students are a very basic student in learning English. That is why an English teacher should use alternative assessments in teaching. For this reason, the author chose the elementary school as the subject of this study. The author wants to know how the impact of alternative assessment in the classroom of the English language. To do so, the author gained the data in-depth interview by giving questionnaires using a structured questionnaire technique. Further, the analysis reveals that the English teacher adds an alternative assessment because the students do not feel bored with the assessment given by the teacher. Moreover, if the student gets a different assessment, the teacher can see the talent that the students have. The result found that the students’ experience after the English teacher uses alternative assessments are that the students are more appealing and more interested. It also motivates almost all of the students and gives an important learning style. In addition, this report shows that students demonstrate a willingness to perform well in the classroom particularly, preparing a lesson.